Pendampingan Pembuatan SOP untuk Meningkatkan Kualitas Pelayanan Konsumen di Albania Coffe & Resto Kabupaten Kendal - Dyah Purwaningrum; Galih Panjalu Pramono (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
In an effort to improve the quality of service, supporting facilities and infrastructure are needed in the service process provided. Where, there needs to be proper treatment starting from input, process, to output of the service provided. In the service industry, there are many different behaviors from consumers related to the services provided, therefore service companies are expected to always understand and fulfill consumer demand so as to provide satisfaction to their customers. (1) Realizing the importance of loyalty in improving service, Customer loyalty can arise because customers are satisfied with the quality of the product or the quality of service from the product which then customers tend to be loyal for a long time and will make repeat purchases when the company produces new products or repairs its old products, Loyal customers do not just stop at using the same product, but will continue the action, namely by making recommendations for the products they have consumed to others (2) This activity aims to create a strong and sustainable relationship between two parties, be it a company with consumers or a company with employees. increase a sense of ownership and responsibility for the sustainability of the company. And towards achieving the company's vision and mission The method in implementing this PKM activity is in the form of lectures, discussions about the quality of service and good employee loyalty at Albania coffee & Resto in Kendal Regency, this Community Service Activity is related to assisting in the preparation of employee work SOPs with the hope of being able to provide real benefits for progress. The output produced is an accredited community service journal.